Tanggung Jawab Sosial Bank Syariah Terhadap Stakeholder dalam Perspektif Maqâshid Syarî’ah - Siti Amaroh (Universitas Islam Negeri Jakarta, 2016)
The implementation of social responsibility is not solely to meet the expectations of the public, but as a form of devotion to Allah. Good values in social responsibility are shown for the formation of a physically and morally prosperous society, as well as to achieve happiness (fâlah) in the world and the hereafter. Activities of Islamic banks is not only to maximize financial profit but also to achieve social welfare as an effort to fulfill the maqâshid syarî’ah. Therefore, a policy of social responsibility of Islamic banks should be legally integrated in their operational systems and as an obligatory mandate to optimize achievement.DOI: 10.15408/ajis.v16i1.2894